Knowledge in an uncertain world - Fantl, Jeremy; McGrath, Matthew (Oxford : Oxford University Press, 2010)
This study explores the relation between knowledge, reasons and justification. It argues that you can rely on what you know since what you know can be a reason you have and you can rely on your reasons. But the assumption that knowledge allows for a chance of error makes this a controversial position in epistemology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of